Factors Affecting Influenza and Pneumococcal Vaccination Rates in Hemodialysis Patients: A Multicenter Study - Selen T; Merhametsiz Ö; Öneç K; Ercan Z; İslam M; Altun G; Pınar M; Demir ME (Risk Management and Healthcare Policy)
Tamer Selen,1 Özgür Merhametsiz,2 Kürşad Öneç,3 Zafer Ercan,4 Mahmud İslam,4 Gülşah Altun,3 Musa Pınar,4 Mehmet Emin Demir5 1Nephrology Department, Düzce Atatürk State Hospital, Düzce, Turkey; 2Nephrology Department, Yeniyüzyıl University Private Gaziosmanpaşa Hospital, Istanbul, Turkey; 3Nephrology Department, Düzce University Faculty of Medicine Hospital, Düzce, Turkey; 4Nephrology Department, Sakarya University Education and Research Hospital, Sakarya, Turkey; 5Nephrology Department, Atılım University Medicana International Ankara Hospital, Ankara, TurkeyCorrespondence: Tamer Selen, Düzce Atatürk State Hospital, Nephrology Department, Aziziye, Şht. Ramazan Gel Cd. No: 7, Merkez/Düzce, 81010, Türkiye, Email tamer_selen_@hotmail.comPurpose: In patients with end-stage renal disease (ESRD), infections, particularly pneumonias, are the most common cause of hospital admissions and death after cardiovascular diseases. It is recommended that dialysis patients receive the pneumococcal vaccine every five years and the influenza vaccine annually. Our study aims to determine the awareness and factors affecting influenza and pneumococcal vaccination rates in hemodialysis patients.Patients and Methods: This cross-sectional study was conducted on patients undergoing regular hemodialysis treatment in 10 different hemodialysis centers across 4 cities. After excluding patients with less than one year of hemodialysis duration and those under 18 years of age, 548 patients were included in the study. Patients were administered a 20-item survey via face-to-face interview and electronic medical records.Results: Out of the 548 patients, only 19 (3.5%) had knowledge about the pneumococcal vaccine, while 238 (43.4%) had knowledge about the influenza vaccine. There were 220 patients (20.1%) who had knowledge about both vaccines. Among the patients, 95 (17.3%) had received the pneumococcal vaccine, with 41.1% of them having received it five years ago or more. A significant proportion (33.7%) of the patients could not recall the timing of their vaccination. While 183 (33.4%) patients had not received the influenza vaccine, only 140 (25.5%) had been vaccinated regularly every year. The reasons for not receiving the influenza and pneumococcal vaccines were stated as “I do not feel the need because I do not get the flu“ (25%) and ”I do not know about the pneumonia vaccine” (36.7%), respectively. The ROC curve analysis for the influenza questionnaire score showed an AUC of 0.822 (95% CI 0.787– 0.856), with a p-value of < 0.001. The statistically significant cutoff value for predicting influenza vaccination was determined to be 2.5. In the univariate analysis, dialysis duration (HD duration), diabetes mellitus (DM), and vascular access type were found to be statistically significant. In the multivariate logistic regression analysis, dialysis duration and DM were identified as independent factors predicting a higher level of knowledge about the influenza vaccine (p=0.009, 0.003, and p=0.041). The ROC curve analysis for the pneumococcal questionnaire score showed an AUC of 0.920 (95% CI 0.886– 0.955), with a p-value of < 0.001. The statistically significant cutoff value for predicting pneumococcal vaccination was determined to be 3.5. In the univariate analysis, residence, dialysis duration, and education level were found to be statistically significant. In the multivariate logistic regression analysis, dialysis duration and education level were identified as independent factors predicting a higher level of knowledge about the pneumococcal vaccine (p=0.038, 0.040, and p=0.010).Conclusion: It was observed that awareness and vaccination rates regarding influenza and pneumococcal vaccines were lower in our patients than recommended. We believe that educating patients about vaccines and increasing the sensitivity of hemodialysis physicians, nurses and nephrologists on this issue will increase vaccination rates.Keywords: hemodialysis, influenza, pneumococcal pneumonia, vaccine